Wrong Education Accepted By Raizo In James Mcteigue's Ninja Assassin Movie (2009) : An Individual Psychological Approach - FITRIANDONO, EMIKA BAYU (2012)
This study investigates the wrong education by Raizo that is reflected in Ninja Assassin movie viewed from individual psychological approach. The aims of this study are to analyze the structural elements of the movie and to analyze the movie based on individual psychological perspective. This study belongs to qualitative study. In this method, the writer uses two types of data sources, namely primary and secondary data sources. The primary data sources and the object of the study is the movie itself, meanwhile the secondary one is any literature related to this study for example reading some other resources related to the movie. The writer collects the data from both primary and secondary data source in sort of document as evidence. The technique of analyzing data is descriptive. Based on the analysis, the writer concludes that wrong education accepted by Raizo in Ninja Assassin movie is influenced by several aspects. They are fictional finalism, inferiority feeling, striving for superiority, style of life, social interest and creative power. The six elements above have closed relationship. Raizo has right education from his friend, Kiriko. He has to control his inferiority feeling to stop Clan Ozunu so he had to leave it. He is striving for superiority, has a useful social type, low social interest and he has creative power. All of six elements above are needed by Raizo for achieving his goal. Based on Individual Psychological aspects shown in the Movie, the writer then concludes that literary work reflects the condition of people who have right of education in their life.